Anodic behavior of passive metals and their alloys in chloride solutions - Tovkes, V.V.; Smirnova, O.L.; Bairachnyi, B.I. (Functional Materials, 2007)
Kinetic laws of anodic processes on stainless steel have been investigated by considering dynamic and static polarization measurements. The passive state caused by presence of a dense oxide film on steel surface has been established to be broken in hydrochloric acid solution. The steel polarization by direct currents is characterized by transition in an active condition and allows to obtain an active surface. The galvanostatic mode with maintenance of constant anodic current density (up to 5.10⁻³ A/cm²) promotes selective dissolution of the steel with etching chrome as the most electronegative component, thus, formation of an active micro-rough surface is observed.